2021
DOI: 10.3389/fcell.2021.636615
|View full text |Cite
|
Sign up to set email alerts
|

Unpicking the Roles of DNA Damage Protein Kinases in Trypanosomatids

Abstract: To preserve genome integrity when faced with DNA lesions, cells activate and coordinate a multitude of DNA repair pathways to ensure timely error correction or tolerance, collectively called the DNA damage response (DDR). These interconnecting damage response pathways are molecular signal relays, with protein kinases (PKs) at the pinnacle. Focused efforts in model eukaryotes have revealed intricate aspects of DNA repair PK function, including how they direct DDR pathways and how repair reactions connect to wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…Apart from Ku70/80 and DNA-PKcs, core NHEJ proteins are absent in most organisms belonging to the excavata group. A recent evolutional analysis of DNA-PKcs identified its orthologs in a wide range of eukaryotes including Naegleria gruberi (Lees-Miller et al, 2021) and Leishmania major (Silva et al, 2021). In addition, we found that Trypanosoma cruzi has a putative DNA-PKcs ortholog that does not have the FAT, kinase and FATC domains but the heat-repeat domain, of which fold is predicted to be similar to that of human DNA-PKcs (Figure 1; Figure S1b).…”
Section: Overview Of the Conservation Pattern Of Nhej Proteinsmentioning
confidence: 66%
“…Apart from Ku70/80 and DNA-PKcs, core NHEJ proteins are absent in most organisms belonging to the excavata group. A recent evolutional analysis of DNA-PKcs identified its orthologs in a wide range of eukaryotes including Naegleria gruberi (Lees-Miller et al, 2021) and Leishmania major (Silva et al, 2021). In addition, we found that Trypanosoma cruzi has a putative DNA-PKcs ortholog that does not have the FAT, kinase and FATC domains but the heat-repeat domain, of which fold is predicted to be similar to that of human DNA-PKcs (Figure 1; Figure S1b).…”
Section: Overview Of the Conservation Pattern Of Nhej Proteinsmentioning
confidence: 66%
“…Apart from Ku70/80 and DNA‐PKcs, core NHEJ proteins are absent in most organisms belonging to the excavata group. A recent evolutional analysis of DNA‐PKcs identified its orthologs in a wide range of eukaryotes including Naegleria gruberi (Lees‐Miller et al., 2021) and Leishmania major (Silva et al., 2021). In addition, we found that Trypanosoma cruzi has a putative DNA‐PKcs ortholog that does not have the FAT, kinase and FATC domains but the heat‐repeat domain, of which fold is predicted to be similar to that of human DNA‐PKcs (Figure 1; Figure S1b).…”
Section: Resultsmentioning
confidence: 99%